Sexual Harassment in Public Spaces and Police Patrols: Experimental Evidence from Urban India - Sofia Amaral; Girija Borker; Nathan Fiala; Anjani Kumar; Nishith Prakash; Maria Micaela Sviatschi (The Quarterly Journal of Economics, 2025)
Abstract We conduct a randomized controlled trial to evaluate the effect of an innovative police patrol program on sexual harassment in public spaces in Hyderabad, India. In collaboration with the Hyderabad City Police, we randomize exposure to police patrols and the visibility of officers by deploying both uniformed and undercover officers across 350 hot spots. To assess the effect, we implement a novel, high-frequency observation exercise to measure sexual harassment at these hot spots, where enumerators recorded all observed instances of sexual harassment and women’s responses in real time. We find that although police patrols had no effect on overall street harassment, uniformed police patrols reduced severe forms of harassment (forceful touching, intimidation) by 27% and reduced the likelihood of women leaving the hot spot due to sexual harassment. We uncovered the underlying mechanisms and found that both police visibility and officers’ attitudes toward sexual harassment are key to understanding its incidence.